Next Generation DNA Led Technologies - Avadhanam, Sharada; Jyothsna, G.; Kashyap, Amita; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This brief highlights advances in DNA technologies and their wider applications. DNA is the source of life and has been studied since a generation, but very little is known as yet. Several sophisticated technologies of the current era have laid their foundations on the principle of DNA based mechanisms. DNA based technologies are bringing a new revolution of Advanced Science and Technology. Forensic Investigation, Medical Diagnosis, Paternity Disputes, Individual Identity, Health insurance, Motor Insurance have incorporated the DNA testing and profiling technologies for settling the issues.
Crime scene forensic evidence as trace DNA profiling solves the case -- A rape on a minor victim under POCSO act 2012 investigation through DNA analysis technique -A Case Study -- Study of Genetic Polymorphism at 9 STR Loci in the Jat Sikh Population of Madhya Pradesh -- Allele frequency distribution and Genetic Structure of Bhil Tribes of Madhya Pradesh based on 15 Autosomal and 12 X STR loci -- CYP Polymorphism and Its Association with Tobacco Usage and Susceptibility to Head and Neck Cancer -- Brain Computer Interface Used in Health Care Technologies -- Novel Topical Gel Formulation of Hamiltonia Suaveolens for wound Healing Activity -- Neural Network Based Rule Extraction for analysing risk factors and stages in Cervical Cancer - An Analytical Study -- Evaluation of Nutraceuticals in Fruit Extracts of Psidium guajava L -- EMG Signals Characterization in Three States of Contraction by Neuro- Fuzzy Network and Feature Extraction -- A pilot study on assessment of Triplet repeat primed PCR for fragile X syndrome diagnosis -- DNA-Binding and Antimicrobial Studies of Molybdenum Complexes -- Acclimatization of invitro Propagated Banana Grand Naine by Biotinization - Survival Rate by Phenol Concentrations -- Biopriming of micropropagated plantlets using various bacterial strains in different combinations-induces the systemic resistance -- Insilico Characterization of The Mutational Hotspot Regions of The Enzyme Protease and An Insight to The Effect of These Mutations on The Stability of The Protein -- Quality Improvement of Poultry Feed by Chelated Micronutrients.
Keywords: Biomedical engineering; Forensic sciences; Bioinformatics; Computational intelligence; Biomedical Engineering and Bioengineering; Forensic Science; Bioinformatics; Computational and Systems Biology; Computational Intelligence